(3MGTjI eYGde GdOjfs - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
.. (3fMh CcdJ NHRG hbdJ bhdG EdG EPG cGfJ bQjfI fMh bhdg JYGdi (B" (3hCfRdfG ef GdSeGA eGA WghQG (B" .. (3GdSGOS GdLfS ajg ajajO GdYehe fMh bhdg JYGdi (B" (3CMd Gddg GdHjY (B"...s
(3BNQgG (B:s
... (3eKd GdeMbb hGdYdGeI GdfGbd dgPG GdGJaGb aEf CQjO efg eGgh GdeUWdM YfOfG de jdRe JYOO GdMhGOK hEf CQjO efg ZjQg dReg JYOO GdMhGOK hGdfbd hGdCUd YOeg abO jbY (B....s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 543s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs